2014
DOI: 10.1021/jp405035x
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Specific Effects on the Assembly of Collagen Layers Mediated by Magnesium Ion on Mica Surface

Abstract: The well-ordered assembly of collagen molecules on mica surface has attracted extensive attention because it has great potential applications or can be served as a model system for study on the assembly process. Although the epitaxially guided collagen assembly mediated by potassium ion on mica surface has been reported several times over these years, specific effects of anions in this field has never been surveyed and discussed before now. In this work, atomic force microscopy was employed to visually follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 36 publications
2
27
0
1
Order By: Relevance
“…Pi supplementation). Moreover, it has been reported that Mg 2+ salts can modify collagen assembly [23]. Consistently, we have noticed a striking effect of MgCl 2 on size and organization of collagen fibrils.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pi supplementation). Moreover, it has been reported that Mg 2+ salts can modify collagen assembly [23]. Consistently, we have noticed a striking effect of MgCl 2 on size and organization of collagen fibrils.…”
Section: Discussionsupporting
confidence: 91%
“…, glycosaminoglycans) [18,19,20,21], all experimental conditions were accurately controlled. In the present study, MgCl 2 was also added to the collagen solution (Figure 1) since it has been suggested that magnesium: (i) interferes with mineral deposition possibly preventing ectopic calcification [22]; (ii) can be a modifier of collagen assembly [23]; and (iii) is present in calcified nodules in clinical contexts [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the effects of Na + and Mg 2+ on collagen selfassembly were typically chaotropic and will cause collagen assembly homogeneous dense network or flat membrane and the increase of collagen solubility. In this study, Hofmeister series [11] and Collins' model [12][13][14][15] were used to explain the interaction mechanism of collagen and different cations at the molecular level. It provides theoretical guidance and data supports for the biological, medical, food, and cosmetic manufacturing industries.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of papers involved in Hofmeister series related to various fields especially biomedicine are large and still keep growing every year [8][9][10]. Wang et al demonstrated a sequence (SO 4 2− > Ac − > Cl − ) which has the stabilizing and salting-out effects on proteins and macromolecules [11]. Acetate was selected to investigate the effect of cations on 2 Journal of Food Quality collagen self-assembly in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of magnetic beads into a collagen solution has also been investigated as means to produce aligned thin and thick hydrogels . Alternative, yet underinvestigated methods to produce aligned collagen hydrogels include molecular crowding, dynamic shear, mica surfaces, mechanical loading, centrifugation, followed by self‐assembly at 37 °C, and cyclic stretching …”
Section: Self‐assemblymentioning
confidence: 99%